2017
DOI: 10.1136/postgradmedj-2017-135233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prescription medications on erectile dysfunction

Abstract: Erectile dysfunction (ED) affects about 50% of men in the USA and is primarily attributed to physiological (organic) and psychological causes. However, a substantial portion of men suffer from ED due to iatrogenic causes. Common medications such as antihypertensives, non-steroidal anti-inflammatory drugs and antacids may cause ED. Physicians should be aware of the various prescription medications that may cause ED to properly screen and counsel patients on an issue that many may feel too uncomfortable to discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 97 publications
1
15
0
Order By: Relevance
“…Patients who discontinue these medications because of adverse effects can experience detrimental psychiatric outcomes. 4 Neuropsychiatric medications have a variety of adverse effects due to the multiple receptors targeted throughout the body. These receptors include central and peripheral serotonergic, adrenergic, dopaminergic, cholinergic, histaminergic, and melanocortin receptors.…”
Section: Neuropsychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who discontinue these medications because of adverse effects can experience detrimental psychiatric outcomes. 4 Neuropsychiatric medications have a variety of adverse effects due to the multiple receptors targeted throughout the body. These receptors include central and peripheral serotonergic, adrenergic, dopaminergic, cholinergic, histaminergic, and melanocortin receptors.…”
Section: Neuropsychiatrymentioning
confidence: 99%
“…In an age when about 60% of the population reports prescription drug use in a given year, medication-induced ED is an important organic cause of ED. 4 It is estimated that up to 25% of all ED is related to medication use and may be reversible. 5 It is incumbent on physicians to be familiar with these medications.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of risk factors for ED, including age, obesity, smoking, depression, hypertension, various medications, history of pelvic surgery, spinal cord lesions and psychological variables (Razdan et al, 2018). In this respect, many common conditions like depression and widely used medications are related to the aetiology of ED (Nguyen et al, 2017).…”
Section: C-reactive Protein-albumin Ratio and Erectile Dysfunctionmentioning
confidence: 99%
“…It is associated with underlying comorbidities such as cardiovascular disease [ 2 ] and metabolic syndrome [ 3 ], and it has been shown that men with ED have a significantly higher chance of a cardiovascular event in the years following diagnosis [ 4 ]. Multiple factors may contribute to ED, including hypertension [ 5 ], diabetes [ 6 ], psychological disorders [ 7 ], medications [ 8 ], hypogonadism [ 9 ], and sleep disorders [ 10 ].…”
Section: Introductionmentioning
confidence: 99%